Design of fluid thermal systems - Janna, William S. (Cengage Learning, 2015)
This book is designed to serve senior-level engineering students taking a capstone design course in fluid and thermal systems design. It is built from the ground up with the needs and interests of practicing engineers in mind; the emphasis is on practical applications